Ocular doppler imaging: opening a new window in decoding glaucoma - Senger, K. P. S.; Anand, A. K.; Singh, Ankita; Sharma, Vivek; Patiyal, S. (International Journal of Research in Medical Sciences, 2019)
Background: In the aetiopathogenesis of multifactorial glaucoma autoregulation of ocular blood flow plays an important role as failure of autoregulation may lead to progression of disease. Aim of this study to understand this better this study was designed to investigate the quantum of these abnormalities and their likely role in pathogenesis and prognosis of primary open angle glaucoma(POAG). Methods: This is a case control study design which involved 67 POAG patients and 67 matched controls. The parameters assessed includes peak systolic velocity(PSV), end diastolic velocity(EDV) and resistive index(RI) of ophthalmic artery(OA) and central retinal artery(CRA) of patients having POAG with age and sex matched healthy subjects. The data obtained was statistically analysed using IBM SPSS 21. Results: The study showed decreased PSV of 31.7 cm/s vs 42.7 cm/s(p=0.0001) and EDV11.7 cm/s vs 19.8 cm/s(p=0.002) with increased RI 0.63 vs 0.53(p=0.000) in OA and PSV of 15.2 cm/s vs 21.4 cm/s(p=0.001) and EDV4.7 cm/s vs 11.7 cm/s(p=0.003) with increased RI 0.69 vs 0.45(p=0.000) in CRA in both eyes in POAG patients as compared to healthy controls. Conclusion: The study has shown the promising application of ocular Doppler in evaluating POAG patients. However, more such studies are needed with larger study sample and on follow up basis for better understanding glaucoma hemodynamics and applicability of ocular Doppler in management of glaucoma.